2018
DOI: 10.1111/nmo.13500
|View full text |Cite
|
Sign up to set email alerts
|

Targeting epigenetic mechanisms for chronic visceral pain: A valid approach for the development of novel therapeutics

Abstract: Background Chronic visceral pain is persistent pain emanating from thoracic, pelvic, or abdominal origin that is poorly localized with regard to the specific organ affected. The prevalence can range up to 25% in the adult population as chronic visceral pain is a common feature of many visceral disorders, which may or may not be accompanied by distinct structural or histological abnormalities within the visceral organs. Mounting evidence suggests that changes in epigenetic mechanisms are involved in the top‐dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 160 publications
0
15
0
Order By: Relevance
“…With the rapid development of treatments, acting through modulation of epigenetic modifications, our approach may turn out to be promising. 44…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of treatments, acting through modulation of epigenetic modifications, our approach may turn out to be promising. 44…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory and anti-fibrogenesis role of givinostat has been revealed in several acute liver disease models, yet whether HDAC inhibitors could alleviated inflammation and fibrosis in chronic disease requires further study. Recent studies have demonstrated that givinostat could interfere inflammation and fibrosis progression in different diseases like intestinal epithelial inflammation or osteoarthritis (39,40). This prompted us to examine whether givinostat could serve as a potential candidate for treatment of NASH, which remains undetermined up to now.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing strong opioids in patients with chronic pain requires precision in management. Both genetic and epigenetic factors contribute to the development of drug resistance in patients with chronic pain (6,7). Genetic variation in receptors contributes to the various responses to opioids within or between individuals (8).…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%